Kontribusi Pemanfaatan Ubi Jalar Ungu Menjadi Klepon Di Kota Bengkulu - Anggraini, Sentri; Aristina, Selvin; Ilahi, M Dellan Anugrah; Pratama, Aldi Agung; Sahputra, Ikwan; Saputra, Zony Hendra; Sumartono, Eko (Jurnal PADAMU NEGERI (Pengabdian pada Masyarakat Bidang Eksakta), 2023)
Tubers, one of which is sweet potato, is one of the local food production from plantations and agriculture in Bengkulu City.The potential of sweet potato as a raw material for the food industry is very large, given the abundant material resources available, due to easy cultivation and a short harvest period.Purple sweet potato is a food ingredient that has a high content of carbohydrate nutrients and a source of calories. Therefore, in some areas sweet potatoes are also used as a staple food. Sweet potatoes are also a source of vitamins and minerals. Vitamins contained in sweet potatoes are vitamin C and rich in vitamin A (beta-carotene), thiamin (vitamin B1) and riboflavin. While the minerals in sweet potatoes include iron (Fe), phosphorus (P) and calcium (Ca). The purpose of this activity is to process purple sweet potato into klepon which has a unique variation. Because klepon is generally green and filled with brown sugar and topped with grated coconut, various types of klepon made with several ingredients certainly have their own charm, especially regarding color. Purple sweet potato will give the klepon a natural purple color, and we also vary the klepon filling with chocolate bars and topped with chocolate mesis and grated cheese.Â